Imitation of lateralised body movements: doing it the hard way. - Press, C; Ray, E; Heyes, C (2009)
Two experiments examined imitation of lateralised body movement sequences presented at six viewing angles (0 degrees , 60 degrees , 120 degrees , 180 degrees , 240 degrees , and 300 degrees rotation relative to the participant's body). Experiment 1 found that, when participants were instructed simply to "do what the model does", at all viewing angles they produced more actions using the same side of the body as the model (anatomical matches), than actions using the opposite side (anatomical non-matches). In Experiment 2 participants were instructed to produce either anatomical matches or anatomical non-matches of observed actions. When the model was viewed from behind (0 degrees ), the anatomically matching group were more accurate than the anatomically non-matching group, but the non-matching group was superior when the model faced the participant (180 degrees and 240 degrees ). No reliable differences were observed between groups at 60 degrees , 120 degrees , and 300 degrees . In combination, the results of Experiments 1 and 2 suggest that, when they are confronting a model, people choose to imitate the hard way; they attempt to match observed actions anatomically, in spite of the fact that anatomical matching is more subject to error than anatomical non-matching.